2022
DOI: 10.3390/biomedicines10102439
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Therapeutic Effects in Inflammatory Bowel Diseases: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: (1) Introduction: Inflammatory Bowel Disease (IBD) patients may benefit from cannabinoid administration supplementary therapy; currently no consensus on its effect has been reached. (2) Methods: a systematic review of RCTs on cannabinoid supplementation therapy in IBD has been conducted; data sources were MEDLINE, Scopus, ClinicalTrials.gov. (3) Results: out of 974 papers found with electronic search, six studies have been included into the systematic review, and five of them, for a grand total of 208 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It is possible that cannabinoids do not have much of an effect on disease activity parameters that relate to inflammation. Both Doeve et al and Vinci et al concluded similarly, reporting little to no impact of cannabinoids on remission or inflammatory biomarkers 29,30 . In contrast, recent studies in animal models of intestinal inflammation have shown a reduction in colonic inflammation, with degrading enzymes for endocannabinoids; such as fatty acid amide hydrolase inhibitors and cannabidiol 37,38 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is possible that cannabinoids do not have much of an effect on disease activity parameters that relate to inflammation. Both Doeve et al and Vinci et al concluded similarly, reporting little to no impact of cannabinoids on remission or inflammatory biomarkers 29,30 . In contrast, recent studies in animal models of intestinal inflammation have shown a reduction in colonic inflammation, with degrading enzymes for endocannabinoids; such as fatty acid amide hydrolase inhibitors and cannabidiol 37,38 .…”
Section: Discussionmentioning
confidence: 90%
“…Two systematic reviews without pooling of results, and two meta-analyses with high heterogeneity (with both observational and interventional studies) have already been performed to assess the efficacy and safety of cannabinoids in UC [27][28][29][30] . However, results have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, there is no strong evidence concerning this valuable objective in the long term [3]. Thus, in this holistic strategy, an integration between conventional therapy, biological therapy, nutritional/supplementation intervention and surgery are the therapeutic tools that must be carefully selected on a case-by-case basis [1], [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this holistic strategy, integration between conventional therapy, biological therapy, nutritional/supplementation intervention and surgery is the therapeutic tool that must be carefully selected on a case-by-case basis [ 1 , 4 – 7 ].…”
Section: Introductionmentioning
confidence: 99%